ANALISIS KONSEP DESAIN HYBRID PADA MASJID AGUNG JAWA TENGAH (TINJAUAN ASPEK RUANG DAN BENTUK ) - Ikhwanuddin, Ikhwanuddin (Nalars, 2011)
ABSTRAK. Desain arsitektur perlu memperhatikan sejarah dan budaya lokal, agar karya-karya arsitektur tidak asing berada di tempatnya dan sekaligus tetap memiliki karakternya yang unik. Salah satu cara untuk mendesain karya-karya berkarakter lokal dan unik adalah dengan menggunakan konsep desain Hybrid. Gagasan pokok konsep desain  Hybrid adalah mencampur atau  menggabungkan dua hal (referensi arsitektur) yang berbeda untuk menghasilkan sesuatu yang baru. Oleh sebab itu, konsep desain ini sangat menarik untuk diteliti. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Obyek penelitian adalah Masjid Agung Jawa Tengah (MAJT). Lokasi obyek penelitian berada di kota Semarang, Jawa Tengah. Teknik pengambilan data primer dengan survei (observasi dan dokumentasi). Data sekunder berupa gambar perencanaan. Teknik analisis data dengan analisis grafis. Hasil penelitian menunjukkan bahwa metode hybrid diterapkan pada desain MAJT, baik pada aspek bentuk maupun ruang.Pada aspek bentuk berupa mixing atau percampuran antara bentuk-bentuk elemen arsitektur masjid  Timur Tengah dan arsitektur tradisonal Jawa.mixing elemen arsitektur ini terdapat pada: a) atap masjid, b) interior ruang utama sholat,dan c) elemen penting lainnya, seperti: plafond mezanin, kolom-kolom  dan menara masjid.  Sedangkan pada aspek ruang, diterapkan konsep desain: a) dominasi organisasi ruang masjid tradisional Jawa pada ruang sholat utama, b) ambiguity pada serambi masjid, dan c) displacing beberapa elemen penting masjid.  Kata Kunci: mixing, ambiguity, displacing  ABSTRACT. The architectural design needs to consider the local history and culture, thus architectural masterpieces will not become out of place within their location and will have unique character. How to design masterpieces which have local and unique character is by using Hybrid design concept. Hybrid design concept main idea is to mix or combine the two things (reference architecture), which is different to produce something new. Therefore, this design concept is very interesting to study. The paradigm of research is rationalism. A research using a grand concept. The case of research is Central Java Province Great Mosque (CJP-GM). The location of object lay on street of Gajahmada in Semarang City, capitol of central Java Province. The data is qualitative one and the method of collecting data is survey. The data have been analyzed using graphical method. The results of research show that hybrid design concept is used in formal aspect and space one of researched object. In formal aspect is used mixing method between arabic mosque (ottoman type) and javanese traditional mosque. The method was used in several ways: a) on the roof. It is used the principal of equivalent-mixing by wrapping and simplicity technique to form roof of CJP-GM, b) in interior of haram. it  used the principal of dominant-mixing to create the haram interior. The affect of javanese traditional mosque is strong enough in creating interior sense than arabic mosque, c) ambiguity principal is used in creating the form of Serambi of CJP-GM by cutting the Shan form. For the space aspect, it used some  methods: a) organisational space. The organisational space of Javanese traditional mosque is used as the rule to organize the space of CJP-GM, but the one space, called serambi (front porch), is modified in touch of an arabic mosque space, b) serambi of mosque. The space of Serambi is formed using ambiguity methods. The technique of placing-displacing is treated between serambi and shan, and the merging technique is treated berween shan and pelataran, c) the wudlu place and bedug. Both of them  are important elements in javanese traditional  mosque. Both element are treated with displacing technique. By this technique, both elements are placed differently from javanese traditional mosque. Keywords: mixing, ambiguity, displacing